Identification of a VO2 deflection point coinciding with the heart rate deflection point and ventilatory threshold in cycling - Grazzi, G.; Mazzoni, G.; Casoni, I.; Uliari, S.; Collini, G.; van der Heide, L.; Conconi, F. (The Journal of Strength and Conditioning Research, 2008)
The purposes of this study were to compare the patterns of the work rate (WR)-VO2 and WR-heart rate (HR) relationships in incremental cycling, to ascertain the occurrence of a VO2 deflection (VO2def) coinciding with the HR deflection point (HRdef ), and to determine whether the VO2def, if present, coincides with the ventilatory anaerobic threshold (VT). Twenty-four professional cyclists performed a maximal incremental test on a wind-load cycle ergometer. Work rate, HR, VO2, and VCO2 were recorded. The WR-VO2 relationships obtained were linear up to submaximal WR and curvilinear thereafter and thus described a VO2def. The WR and VO2 at VO2def were mathematically determined for all subjects. The ratio of [DELTA]WR/[DELTA]VO2 up to VO2def was significantly lower than that above VO2def (90 +/- 11 W/L.min versus 133 +/- 35 W/L.min, p < 0.0001). The WR-HR relationships obtained were linear up to submaximal WR and curvilinear thereafter. The WR and HR at HRdef were mathematically determined for all subjects. The WR values at VO2def and at HRdef (329 +/- 32 W and 326 +/- 34 W) were significantly correlated (R2 = 0.96, p < 0.0001) and in good concordance (limits of agreement from -4.7% to 3.2%, Bland-Altman analysis). The VO2 at VT was then determined for all subjects. The VO2 values at VO2def and at VT were significantly correlated (R2 = 0.99, p < 0.0001) and in strong concordance (limits of agreement from -1.9% to 1.0%, Bland-Altman analysis). In conclusion, a VO2def coinciding with HRdef and VT was shown. This confirms that the determination of the WR-HR relationship and of HRdef is a practical and noninvasive means of identifying anaerobic threshold.